2002
DOI: 10.1523/jneurosci.22-06-02237.2002
|View full text |Cite
|
Sign up to set email alerts
|

cAMP/Ca2+Response Element-Binding Protein Function Is Essential for Ocular Dominance Plasticity

Abstract: The monocular deprivation model of amblyopia is characterized by a reduction in cortical responses to stimulation of the deprived eye. Although the effects of monocular deprivation on the primary visual cortex have been well characterized physiologically and anatomically, the molecular mechanisms underlying ocular dominance plasticity remain unknown. Previous studies have indicated that the transcription factor adenosine cAMP/Ca(2+) response element-binding protein (CREB) is activated during monocular deprivat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
72
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(76 citation statements)
references
References 48 publications
(70 reference statements)
4
72
0
Order By: Relevance
“…It is indeed known that CREB/CRE participates in the modulation of plasticity and development of the mouse visual cortex and is also developmentally regulated in the LGN (Huang et al, 1999;Pham et al, 1999;Mower et al, 2002). CREB is activated by neuronal activity (West et al, 2002), and environmental enrichment increases immunoreactivity to CREB in the hippocampus (Williams et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is indeed known that CREB/CRE participates in the modulation of plasticity and development of the mouse visual cortex and is also developmentally regulated in the LGN (Huang et al, 1999;Pham et al, 1999;Mower et al, 2002). CREB is activated by neuronal activity (West et al, 2002), and environmental enrichment increases immunoreactivity to CREB in the hippocampus (Williams et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…An important hub in the development and plasticity of sensory systems and in particular of the visual system is the cAMP/ CREB pathway (Impey et al, 1996;Pham et al, 1999;Barth et al, 2000;Mower et al, 2002;Cancedda et al, 2003). To investigate the involvement of this system in mediating the effects of environmental enrichment on visual system development, we used transgenic mice that carry the LacZ reporter gene under the control of the CRE promoter (Impey et al, 1996).…”
Section: Acceleration Of the Developmentally Regulated Cre-mediated Gmentioning
confidence: 99%
“…90 Another way by which EE can regulate gene expression might be the activation of specific transcription factors. One possibility is that BDNF intracellular signalling stimulates CREB phosphorylation and activation, [91][92][93] which has a pivotal role in various forms of plasticity in the visual cortex [94][95][96] and other brain structures. 97 In line with this hypothesis, it has been shown that EE in adulthood increases immunoreactivity to CREB in the hippocampus as well 98 (Figure 3b).…”
Section: Impact Of Ee On the Brain L Baroncelli Et Almentioning
confidence: 99%
“…A common mechanism through which these molecules might act in ocular dominance plasticity is phosphorylation of the cAMP/ Ca 2ϩ response element-binding protein (CREB), which in turn regulates the transcription of plasticity-related genes (Gonzalez and Montminy, 1989;Deisseroth et al, 1996;Finkbeiner et al, 1997). More recent experiments have indeed shown that CREB function is necessary for the occurrence of an ocular dominance shift during monocular deprivation (Mower et al, 2002).…”
Section: Abstract: Creb; Ocular Dominance Plasticity; Recovery Of Fumentioning
confidence: 99%
“…Vectors expressing CREB and LacZ were used as controls. This methodology is advantageous in that it allows temporally and spatially restricted expression of transgenes while preserving normal visual cortical responses (Mower et al, 2002). Quantitative in vivo recording techniques were then used to assess recovery.…”
Section: Abstract: Creb; Ocular Dominance Plasticity; Recovery Of Fumentioning
confidence: 99%